Analyses Error Grammar in Interview’s Sheni And Ayu On Teams - Sheni, Ibadadilah; Panjaitan, Bella Natasia; Handayani, Nurma Dhona (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
Language is a means of communication for every human being. Also, having several types of languages ??such as regional languages, state languages ??and international languages ??is English. English in general has existed since elementary school to college. Many adults are still wrong in the use of good and correct English so that it requires more extra learning. One method of improving English through vocabulary is speaking like an interview. In the interview, there were also presenters and auditors who interacted with each other. The best interviews mostly speak correct vocabulary and sentences. In this study, researchers took sources from interviews with students from the University of Putera Batam as a team. In this study, the researcher aims to analyze grammatical errors and focus on grammatical errors in presenters, which have been obtained using qualitative descriptive methods. The method of presentation is using descriptive presentation in the form of words or sentences that do not have a percentage or value in the form of numbers, where the researcher analyzes according to the error class category of the data. From the results of this study, the researcher found 15 data where the data consisted of errors of auxiliary verbs and tenses.